2022
DOI: 10.14421/jga.2021.64-04
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Motivasi Keluarga Terhadap Kemampuan Kognitif Anak Usia 5-6 Tahun: Studi Masa Pandemi

Abstract: During the pandemic, children aged 5-6 years need time to learn from home so that cognitive abilities during the pandemic experience obstacles. Family motivation has an important role in empowering children's cognitive abilities. The purpose of this study was to determine the effect of family motivation on the cognitive abilities of children aged 5-6 years during the pandemic. The research method used is quantitative. The research subjects found 60 children consisting and 60 parents of: grades B1, B2, B3, B4 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The last analysis was environment analysis. This analysis is important because inappropriate learning environment may cause serious effects in the learning outcomes (Darimi, 2016;Efiawati, Fauziyah, Syafrida, & Parapat, 2021;Salsabila & Muhid, 2021;Afsari & Khosiah, 2022;Fatmawati & Aziz, 2022). From the environment analysis, the researchers concluded that the learning environment in the targeted population were suitable and appropriate to implement the new approach including STEAM-based learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The last analysis was environment analysis. This analysis is important because inappropriate learning environment may cause serious effects in the learning outcomes (Darimi, 2016;Efiawati, Fauziyah, Syafrida, & Parapat, 2021;Salsabila & Muhid, 2021;Afsari & Khosiah, 2022;Fatmawati & Aziz, 2022). From the environment analysis, the researchers concluded that the learning environment in the targeted population were suitable and appropriate to implement the new approach including STEAM-based learning.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reality is differently showed. Most learning targets especially in early childhood education focus on mastering hard skills rather than soft skills because it is presumably that children have not yet understood ways in mastering soft skills and it is more important to focus on hard skills as the foundation for future development (Budiyono, Husna, & Wildani, 2020;Afsari, Rusdiyani, & Khosiah, 2022). This situation can be seen from previous research conducted in Probolinggo, where showed only 20% early childhood education's teachers understood and willingly to use interactive technology in learning, while the remaining (80%) were reluctant to use digital-based interactive learning media in learning activity (Darimi, 2016;Cahyani & Sulastri, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Children's cognitive development is influenced by environmental factors, both the community and the school environment (AD, 2018;Anida & Eliza, 2020). The child's environment can internalize objects that stimulate cognitive development (Afsari et al, 2022). Literacy in the scientific aspect shows the results of growth and development, which have the widest distribution in several aspects.…”
Section: Discussionmentioning
confidence: 99%
“…There is continuity between aspects of child development. One aspect that must be developed is the cognitive aspect (Afsari et al, 2022;Rahmaniar et al, 2022). Cognitive is a thought process, the ability of individuals to connect, assess and consider an event or event (Juwantara, 2019;Mukhlish Safitri et al, 2020).…”
Section: Introductionmentioning
confidence: 99%